2001
DOI: 10.1088/0957-0233/12/2/301
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of static and dynamic interactions between bubbles and X-hot-film probes

Abstract: Very few investigations of bubbly two-phase flows have used X-hot-film probes for the measurement of the turbulence field in the continuous phase. Therefore the interactions between the sensors of the X probe and the bubbles are not well known and thus can lead to errors in the determination of turbulence parameters. To gain understanding of the interaction, investigations of static and dynamic bubble-sensor interactions were carried out. In the static investigations a probe that is moved through stagnant wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…5 displays image sequences for these three types. These classes correspond to the results of Serizawa et al (1983) and Benk et al (2001), though these authors found a fourth interaction type, namely glancing bubbles. As it is not possible to strictly discriminate between glancing and bouncing hits, we merged these two types.…”
Section: Image Analysis: Types Of Interactionsupporting
confidence: 85%
See 1 more Smart Citation
“…5 displays image sequences for these three types. These classes correspond to the results of Serizawa et al (1983) and Benk et al (2001), though these authors found a fourth interaction type, namely glancing bubbles. As it is not possible to strictly discriminate between glancing and bouncing hits, we merged these two types.…”
Section: Image Analysis: Types Of Interactionsupporting
confidence: 85%
“…These images show that the bubbles are strongly deformed during the interaction. Even when a bubble has already left the probe, shape deformations can be present, see also Benk et al (2001). These surface oscillations, which originate from the bubble-probe interaction, are sometimes very strong.…”
Section: Image Analysis: Types Of Interactionmentioning
confidence: 99%
“…The images given by Rensen et al [31] illustrated that there was a variety of shapes of the signals for the bouncing and splitting bubbles contrasting to the common shape for penetrating bubbles. The video images produced by Benk et al [30] showed that the bubbles were strongly deformed during the interaction with the probe and it became difficult to identify the start and the end of the bubble signal accurately. The dual optical probes for liquid-liquid flow applications were developed by Hamad et al [32] The probe geometry was optimised by studying the signal from the drop-probe interaction.…”
Section: Accuracy Of Experimental Measurementsmentioning
confidence: 99%
“…The drop–probe interaction, which depends on the direction of the drop velocity, may cause more uncertainty for measurements in an inclined pipe due to the change in the flow structure from almost one‐dimensional to three‐dimensional in the inclined pipe. The drop–probe interaction was studied by Benk et al and Rensen et al using a high speed camera to follow the drop movement during the penetration process. They classified bubble–probe interaction into three types: penetrating, splitting and bouncing.…”
Section: Introductionmentioning
confidence: 99%
“…While the terminology differs, all three studies observed bubbles that grazed the probe, wrapped around and bounced off, split, or were penetrated by the probe while remaining intact. Benk et al, 9 who looked at x-wire probes, observed an additional type of collision outcome in which the initial bubble was split into multiple small fragments for large ͑D Ն 3 mm͒, high-speed ͑U bubble Ն 1.8 m / s͒ bubbles ͑We= 124͒. Other studies considered the effects of bubble impacts and deformation on their rise velocity in liquids.…”
Section: Introductionmentioning
confidence: 99%